An Examination of the Principles of the Rule of Law and Their Application in Islam - Balogun, Yisa Olorunda (International Journal of Humanities and Education Development (IJHED), 2023)
A lot of works written on the Rule of Law are without Islamic connotations. The ones with Islamic viewpoints are limited. This article is therefore written to supplement the existing literature on the concept. The paper adopted a qualitative approach and its data was based on secondary sources and content analysis of relevant documents. The article harnesses the available information in the Shar’īah to justify the respect that Islam has for the Rule of Law. In doing this, the researcher examined the various clarifications of law and the Rule of Law, the principles of the Rule of Law and the extent to which these principles are applicable in Islam. It was found out that despite the efforts of Shar’āh and various scholars to sustain the ideal application of the Rule of Law, the concept is still facing numerous challenges, among which are poverty and ignorance, immunities to certain individuals and lack of independence of the judiciary.